HBR's 10 Must Reads on Organizational Resilience - Review, Harvard (Ascent Audio, 2020)
Build resilience in your company to weather the greatest crises. We've combed through hundreds of Harvard Business Review articles and selected the ten most important ones to help your company prepare for and overcome disruption, social upheaval, and disaster. This book will inspire you to: reposition your core business while launching a separate, disruptive business; build the ability to continually anticipate and adjust to emerging trends; prepare for the business implications of climate change; learn about the risks of hyperefficient businesses; develop organizational grit; rebound from a recession faster than your competitors; and lead your company through any kind of crisis.
Online resource; Title from title page (viewed December 29, 2020)
Keywords: Audiobooks; Livres audio